Development of Chemical Protective Clothing Using Multilayer Fabric for Hazardous Chemicals Handling - Nachiappan Sukumar; P. Gananvel; R. Dharmalingam; Sampath Aruna (Journal of Natural Fibers, 2022)
Protection against the safety of people is enforced for the certain occupations when they might be exposed to hazardous chemicals during handling. This research provides an importance of chemical protective clothing, along with its necessity during various industrial applications. The aim of the research is to develop more comfortable and efficient protective cloth for the chemical industry workers. Developed multilayer fabric is to protect them from harmful chemical hazards with five layers, the outer shell made of polyester as it has low absorption and carbon fabric for its higher support. It provides a good strength to the fabric and polyester has a good resistance to lab grade chemicals. The middle layer comprises spun-bonded non-woven sandwiched with carbon fiber. The inner layer is made up of cotton fabric as it gives good absorbency and comfort. In this research, 100% polyester fabric, polyester/cotton fabric and 100% knitted polyester fabric have been used as a comparison in chemical protective clothing. Scanning electronic microscope (SEM) was used to observe the morphology of coated surfaces of protective for process versatility and the highly specific surface area. In this paper, the thermal properties of developed multilayered structures were statistically investigated. The chemical protection, good air permeability, abrasion resistance, fabric stiffness and tearing strength have been performed. The results provide new insights into the development of functional garments/materials and better methods for evaluating the performance of these materials under hazardous work environments.